IMPLEMENTASI MODEL PEMBELAJARAN PROYEK BERBASIS BERMAIN DAN DIGITAL SEBAGAI STRATEGI PENGEMBANGAN KARAKTER MAHASISWA CALON GURU PAUD - Anita Yus; Gita Noveri Eza; Damaiwaty Ray (JURNAL TEMATIK, 2020)
This study aims to determine the implementation of play-based and digital project learning models as a strategy for character development of PAUD teacher candidates. This research is a combination of survey and intervention methods through field experiments. The subjects of this study were a team of instructional lecturers and students who took courses on AUD learning approaches and strategies as many as 90 people. Data were collected using document analysis techniques, observation and questions and answers and analyzed with descriptive statistics and qualitative analysis. The results showed that: (1) learning with play based and digital project models can be used in learning with stages, (a) the initial stage, which consists of developing interests and preparing projects, (b) investigations conducted with field visit activities and discussing activities that have been carried out, and (c) conclusions and results obtained that are carried out with activities that conclude results and present the resulting product; (2) the competencies of students designing learning for AUD are at an average score of 71 and as much as 74% have successfully passed viewed from the design and quality of the video, (3) the play based and digital project learning model can develop the character of responsibility and cooperation